Transcutaneous auricular vagus nerve stimulation improves social deficits through the inhibition of IL-17a signaling in a mouse model of autism - Zhang, Wenjing; Mou, Zhiwei; Zhong, Qi; Liu, Xiaocao; Yan, Lan; Gou, Lei; Chen, Zhuoming; So, Kwok-Fai; Zhang, Li (Frontiers in Psychiatry, 2024)
Maternal exposure to inflammation is one of the causes of autism spectrum disorder (ASD). Electrical stimulation of the vagus nerve exerts a neuroprotective effect via its anti-inflammatory action. We thus investigated whether transcutaneous auricular vagus nerve stimulation (taVNS) can enhance social abilities in a mouse model of ASD induced by maternal immune activation (MIA).ASD mouse model were constructed by intraperitoneal injection of polyinosinic:polycytidylic acid (poly (I:C)). TaVNS with different parameters were tested in ASD mouse model and in C57BL/6 mice, then various behavioral tests and biochemical analyses related to autism were conducted. ASD model mice were injected with an interleukin (IL)-17a antibody into the brain, followed by behavioral testing and biochemical analyses.TaVNS reduced anxiety, improved social function, decreased the number of microglia, and inhibited M1 polarization of microglia. Additionally, taVNS attenuated the expression of the IL-17a protein in the prefrontal cortex and blood of ASD model mice. To examine the possible involvement of IL-17a in taVNS-induced neuroprotection, we injected an IL-17a antibody into the prefrontal cortex of ASD model mice and found that neutralizing IL-17a decreased the number of microglia and inhibited M1 polarization. Furthermore, neutralizing IL-17a improved social function in autism model mice.Our study revealed that reduced neuroinflammation is an important mechanism of taVNS-mediated social improvement and neuroprotection against autism. This effect of taVNS could be attributed to the inhibition of the IL-17a pathway.